Troubling solutions through anthropological fieldwork: Mediation research in Ghana, Australia, and the United States. (November 2021) - Crampton, Alexandra
Social workers and anthropologists encounter different representations of mediation as a professional practice: On the one hand, Social Work is grounded in mediation as expert knowledge that helps others to resolve interpersonal disputes. For example, mediation as Alternative Dispute Resolution (ADR) can enable court cases to resolve without formal trials. On the other hand, Anthropology is grounded in mediation as a research field site and by past intervention experience of anthropologists. As mediation professionalized and became mandated across public institutions, anthropologists became strong ADR critics. Academic debate between mediation proponents and critics ended as critics abandoned research in the 1990s and 2000s. My initial research goal was to pick up from past empirical study. Research was conducted in Australia, Ghana, and the United States in two areas of mediation practice; resolving parenting disputes between adults who are separating or not married, and "elder mediation" cases involving older adults. Initial findings reified past debate through data that supported proponents and critics. Further insight was gained through return to fieldwork using an expanded, ethnographic case study design. This article provides a journey through a seemingly intractable divide that was ultimately resolved through prolonged time in fieldwork focused on understanding client perspectives. I show how social work and anthropology scholars of professional mediation have been positioned on opposite sides of an expert knowledge/fieldwork research boundary. This boundary can be made productive through open exchange about mediation as a practice that evolves through an interplay of expert knowledge, intervention practice, and client engagement.